(untitled) (Modern education and development, 2025)
This article explores the role of digital tools and learner-centered teaching strategies in enhancing the effectiveness of English language instruction. It highlights how technology-driven methods and personalized learning approaches can reshape classroom dynamics, boost learner engagement, and foster the development of communicative competence. By integrating multimedia resources and adaptive teaching models, educators can respond more effectively to students’ individual needs, making the learning experience more interactive, relevant, and outcome-driven. The findings aim to support English educators in designing flexible and impactful teaching environments aligned with 21st-century educational demands.